Analisis Waktu dan Biaya pada Proyek Pembangunan Pasar Induk Senaken Kabupaten Paser dengan Metode Time Cost Trade Off (TCTO) - Erfaliani, Amelia Putri; Pradika, Jermianto Dwi; Hendriyani, Irna; Pratiwi, Reno (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Project management is an effort or activity to planning, leadership, organization and control of company resources to achieve predetermined short-term goals as efficiently and effectively as possible. Optimizing costs and time has many methods that can be used, one of which is often used is Time Cost Trade-Off (TCTO. This method aims to find out how much time and costs are needed to complete the project according to the specified targets. The location of this project is at Senaken Market which is on Jalan Yos Sudarso, Senaken Village, Tanah Grogot District, Paser Regency, East Kalimantan, for Rp. 5.872.872.924,41 and the work duration is 112 days. Alternatives to prevent delays and shorten working time by increasing labor and working hours. From the results of the analysis, it is more effective to increase the number of workers than to increase working hours. The total cost of adding 3 workers is 0.6% less than the total cost of adding 3 hours of work with a work duration of 75 days, 37 days faster than the normal time duration.